2013
DOI: 10.1002/alr.21212
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiologic findings in a case series of maxillary sinusitis of dental origin

Abstract: Background: Maxillary sinusitis of dental origin (MSDO) has been described for decades, but tends to be overlooked as a possible cause of chronic sinusitis by both clinicians and radiologists. The incidence of MSDO in published series is reported to be from 10% to 40% in bacterial sinusitis. We present this series to highlight clinical and radiologic indicators of MSDO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 15 publications
3
96
3
1
Order By: Relevance
“…ODS is diagnosed in a fashion similar to other forms of sinusitis: history to detect sinusitis symptoms, nasal endoscopy to assess for inflammation or infection, and computed tomography (CT) imaging to assess sinusitis extent but also maxillary odontogenic pathology. Sinonasal symptoms of ODS are consistent with cardinal symptoms of acute and chronic sinusitis, although ODS symptoms are more commonly unilateral . Anterior and posterior nasal drainage are most frequently reported in ODS in 60% or more of patients .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…ODS is diagnosed in a fashion similar to other forms of sinusitis: history to detect sinusitis symptoms, nasal endoscopy to assess for inflammation or infection, and computed tomography (CT) imaging to assess sinusitis extent but also maxillary odontogenic pathology. Sinonasal symptoms of ODS are consistent with cardinal symptoms of acute and chronic sinusitis, although ODS symptoms are more commonly unilateral . Anterior and posterior nasal drainage are most frequently reported in ODS in 60% or more of patients .…”
Section: Introductionmentioning
confidence: 75%
“…Sinus CT for ODS often shows maxillary odontogenic pathology, but radiologists frequently overlook the dental pathology . Otolaryngologists must therefore carefully assess maxillary dentition on CT. Additionally, one series found that about one‐third of ODS cases revealed no dental pathology on sinus CT . Sinus cultures in ODS are usually polymicrobial, with a higher likelihood of anaerobes compared with sinogenic sinusitis .…”
Section: Introductionmentioning
confidence: 99%
“…More than 70% of maxillofacial CT scans showing unilateral maxillary sinusitis may be attributable to an odontogenic infection . However, several studies have documented that dental disease may be frequently overlooked on CT by radiologists leading to misdiagnosis . As a result, clinicians should carefully analyze maxillary dentition when interpreting maxillofacial CT scans, particularly in the setting of unilateral maxillary sinusitis .…”
Section: Introductionmentioning
confidence: 99%
“…5,9 Patients who have these underlying disease states may deny sinus symptoms at the time of presentation, yet it has been found that 12 to 65% of patients presenting for maxillary reconstruction exhibit abnormal thickening of the sinus membrane. 1,2,[4][5][6][7][8][9][10]13,14 The hypotheses of this retrospective review of CBCT scans were that 1) sinus membrane thickening is strongly correlated with the health of posterior maxillary teeth and 2) definitive treatment of unhealthy teeth in the posterior maxilla would decrease sinus membrane thickening after 3 to 6 months.…”
mentioning
confidence: 99%